2020
DOI: 10.1021/acsmacrolett.9b01011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dynamics of Confined Polymers near the Immiscible Polymer–Polymer Interface: Neutron Reflectivity Studies

Abstract: For polymer-blend films, local dynamics in confined polymer domains tend to differ from the bulk because of significant contributions from the polymer–polymer interface. Herein, we investigated the diffusion dynamics of entangled polymer thin films confined between different polymers in a direction perpendicular to the surface using neutron reflectivity. We found that a bilayer of poly­(methyl methacrylate) (PMMA) and deuterated PMMA (dPMMA) sandwiched between polystyrene (PS) layers exhibited significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…1 R g away from the PS−PMMA interface. 11 The diffusion dynamics at this position were further accelerated by geometrical confinement, namely, with decreasing thickness of the confined layer. Differently, in this study, the local dynamics were measured by NR as a function of distance from the PS− PMMA interface by changing the thicknesses of PMMA and dPMMA.…”
mentioning
confidence: 96%
“…1 R g away from the PS−PMMA interface. 11 The diffusion dynamics at this position were further accelerated by geometrical confinement, namely, with decreasing thickness of the confined layer. Differently, in this study, the local dynamics were measured by NR as a function of distance from the PS− PMMA interface by changing the thicknesses of PMMA and dPMMA.…”
mentioning
confidence: 96%
“…High-performance multicomponent materials have nanostructured morphologies where the desired global properties are obtained from an amalgam of local property changes caused by the multitude of internal interfaces. Studies on thin polymer films have demonstrated a host of property changes with decreasing film thickness attributed to interface effects, including polymer–polymer interfaces. The efficient design of multicomponent materials requires the understanding of how these interface effects perturb local properties. Glassy–rubbery interfaces between polymer domains impart material toughness and flexibility , and can be used to tune phononic transport .…”
mentioning
confidence: 99%
“…Polymer alloys represented by block copolymers (BCPs) and polymer blends are one of the most widely studied areas in the field of polymer science and engineering. In particular, various studies related to the interface for a phase-separated polymer pair have been conducted from the viewpoint of the miscibility and compatibility. This is because the interfacial structure is of pivotal importance not only for inherent academic interest but also for cutting-edge industrial applications, such as thin film devices, including next-generation lithography, in addition to the traditional ones based on mechanical and optical properties. Polymer chains change the aggregation states at the interface so as to minimize the interfacial energy, which is one of the controlling factors of the interfacial thickness. Thus, it is crucial to obtain a deeper understanding of the phase-separated polymer interface at the molecular level.…”
mentioning
confidence: 99%